Game research by design in project management and beyond - Maria Freese; Geertje Bekebrede (Project Leadership and Society)
Projects are complex systems as they consist of different elements interacting with each other considering a certain degree of uncertainty. Serious games - defined as those that are not primarily intended to entertain - can be used to better understand, analyse, or design projects in such complex socio-technical systems. They are a powerful research method because they provide data and insights into people’s behaviour in relation to their environment. They do this in an engaging way in a safe environment, making them suitable for testing hypotheses and gathering data on choices, decisions, and interactions of people. In addition, serious games provide an environment that allows for mixed methods data collection. This article introduces the Game Research by Design - Approach about the development of serious gaming research set-ups, which addresses three cycles - theoretical, design and empirical one - when conducting research using serious games. This article illustrates the choices researchers need to make when developing research design and experiments based on serious gaming. Further research is needed to elaborate the different steps and to fine-tune this approach.